Diaspora, Desire, and Defiance: A Feminist Reading of Our Sister Killjoy - Dr Twinkle Suri (Journal of International Islamic Law, Human Right and Public Policy, 2026)
This paper examines Our Sister Killjoy by Ama Ata Aidoo as a significant feminist and postcolonial text that foregrounds the question of women’s identity, autonomy, and socio-cultural responsibility. Situating the narrative within the context of African feminism, the study explores the protagonist Sissie’s journey as both a physical and psychological odyssey that interrogates Western materialism, colonial hangovers, and gendered oppression. The paper highlights how Aidoo critiques patriarchal structures embedded in African society while simultaneously exposing the hollowness of Western modernity. Through Sissie’s encounters in Europe and her eventual return to Africa, the novel articulates a resistance to cultural alienation and affirms the importance of rootedness, self-definition, and ideological commitment. Special emphasis is laid on the politics of gender relations, the concept of the “New Woman,” and the interplay between emotional and intellectual autonomy. The concluding section of the novel, particularly “A Love Letter,” is read as a powerful articulation of selfhood, where personal sacrifice becomes a site of resistance and affirmation. The study argues that Aidoo envisions a transformative role for women in postcolonial societies—one that is grounded in cultural consciousness, political awareness, and economic independence. By blending narrative experimentation with ideological critique, Our Sister Killjoy emerges as a compelling text that not only reflects the struggles of African women but also proposes a framework for their emancipation and self-realization.